Handbook of Reliability, Availability, Maintainability and Safety in Engineering Design - Stapelberg, Rudolph Frederick; SpringerLink (Online service) (London : Springer London, 2009)
Handbook of Reliability, Availability, Maintainability and Safety in Engineering Design studies the combination of various methods of designing for reliability, availability, maintainability and safety, as well as the latest techniques in probability and possibility modelling, mathematical algorithmic modelling, evolutionary algorithmic modelling, symbolic logic modelling, artificial intelligence modelling and object-oriented computer modelling, in a logically structured approach to determining the integrity of engineering design. Handbook of Reliability, Availability, Maintainability and Safety in Engineering Design not only encompasses a depth of research into engineering design methods and techniques ranging from quantitative probability theory and expert judgement in Bayesian analysis to qualitative possibility theory, fuzzy logic and uncertainty in Markov analysis; from reliability block diagrams, fault trees, event trees and cause-consequence diagrams to Petri nets, genetic algorithms and artificial neural networks; but it also covers a breadth of research into the concept of integrity in engineering design. Such breadth of research is represented by the inclusion of the topics of reliability and performance, availability and maintainability, and safety and risk, in an overall concept of designing for integrity during the different phases of the engineering design process. These topics add significant value to the theoretical expertise and practical experience of process, chemical, civil, mechanical, electrical and electronic engineers by considering process engineering design from the point of view of "what should be achieved" to meet criteria for designing for reliability, availability, maintainability and safety.
Engineering Design Integrity Overview -- Design Integrity Methodology -- Design Integrity and Automation -- Engineering Design Integrity Application -- Reliability and Performance in Engineering Design -- Availability and Maintainability in Engineering Design -- Safety and Risk in Engineering Design.
Keywords: Engineering; Management; Industrial management; Engineering design; Manufacturing industries; Machines; Tools; Quality control; Reliability; Industrial safety; Civil engineering; Engineering; Quality Control, Reliability, Safety and Risk; Engineering Design; Manufacturing, Machines, Tools; Innovation/Technology Management; Civil Engineering; Electronic books